Carnivores, culture and ‘contagious conflict’: Multiple factors influence perceived problems with carnivores in Tanzania’s Ruaha landscape - Dickman, Amy J.; Hazzah, Leela; Carbone, Chris; Durant, Sarah M (Biological conservation, 2014)
•98.5% of pastoralists and agropastoralists around Ruaha had problems with wildlife.•Large carnivores were viewed as significantly more problematic than other species.•Depredation, religion and ethnicity all affected views towards carnivores.•There was a suggestion of ‘contagious conflict’ between different groups of species.•Conflict mitigation strategies should be broad and aimed at a wide range of taxa. Resolving human-wildlife conflict is a conservation priority, but effective mitigation requires in-depth understanding of the complexity and relative importance of conflict drivers. We conducted 262 semi-structured interviews with villagers around Tanzania’s Ruaha National Park. The surveys provided data on respondents’ perceived problems with wildlife, knowledge, reported killing of carnivores, and their socio-economic characteristics. 98.5% of people perceived a problem with wildlife, and respondents viewed large carnivores as significantly more problematic than other species, due to the threats they posed to livestock and humans. Despite this, only 7.3% of people admitted to having killed any large carnivores. Depredation was widespread, having affected 61.1% of households, but was less important than other forms of stock loss – monthly recall data revealed 1.2% of stock were predated, compared to 9.1% lost to disease and 2.8% to theft. Although experience of depredation significantly predicted negative attitudes towards carnivores, it was not the most important factor. The study raises the possibility of ‘contagious conflict’, where perceived problems with one group of species were strongly associated with perceived problems with others. Furthermore, factors such as ethnic group and religious beliefs were significant predictors of perceived problems. This study suggests that effective conflict mitigation should involve measures to improve attitudes towards a broad range of species, rather than a single taxon, and that action should be taken to also address the social and cultural drivers of conflict, rather than merely focusing upon reducing wildlife damage.